1999
DOI: 10.1097/00004836-199904000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Esophagitis and Gastroesophageal Flap Valve

Abstract: The authors studied the relationship of endoscopic esophagitis and gastroesophageal flap valve (GEFV) in patients with symptomatic gastroesophageal reflux (GER). On endoscopy, the GEFV was graded as I to IV in 138 patients with acid regurgitation and heartburn relieved by antacids, and in 54 control subjects without symptoms suggestive of GER. Grade of GEFV was correlated with the grade of esophagitis, response to medical treatment, duration of symptoms, obesity, smoking, sex, and age of the patient. Abnormal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
28
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 9 publications
8
28
0
1
Order By: Relevance
“…Thus, grading of the GEFV is simple and reproducible, and offers additional useful information for the evaluation of patients with GERD. 6,9,22,23 In the present study, GERD, defined by ambulatory pH monitoring, was found in 35.7% of the normal GEFV group and in 67.3% of the abnormal GEFV group. Our results are similar to those in a previous report 9 that GERD, defined by the presence of abnormal esophageal acid exposure, was found in 33.0% of the normal GEFV group and in 66.7% of the abnormal GEFV group.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Thus, grading of the GEFV is simple and reproducible, and offers additional useful information for the evaluation of patients with GERD. 6,9,22,23 In the present study, GERD, defined by ambulatory pH monitoring, was found in 35.7% of the normal GEFV group and in 67.3% of the abnormal GEFV group. Our results are similar to those in a previous report 9 that GERD, defined by the presence of abnormal esophageal acid exposure, was found in 33.0% of the normal GEFV group and in 66.7% of the abnormal GEFV group.…”
Section: Discussionsupporting
confidence: 55%
“…These findings are consistent with previous reports stating that abnormal GEFV is associated with reflux esophagitis and Barrett's epithelium. 9,22,23 In some prior reports, 22-24 a tendency for an agerelated increase in the prevalence of abnormal GFEV was noted; in another report, 9 there was no difference according to GEFV grade. We also did not observe an association of age with GEFV grade.…”
Section: Discussionmentioning
confidence: 91%
“…To our knowledge, only one previous study has correlated symptoms with grades of GEFV: Contractor et al found that patients with grades III and IV were more likely to have GERD symptoms, but response to medical therapy did not correlate with GEFV grades; however, a long-term on-demand treatment was not used [17].…”
Section: Discussionmentioning
confidence: 95%
“…Based on these observations, Öberg et al 16 concluded that abnormal esophageal acid exposure and esophageal mucosal injury were uncommon in patients with grade 0 gastroesophageal valves, and these findings were therefore predictive of the absence of reflux disease. Contractor et al 17 reported that, the prevalence of abnormal GEFV function was significantly higher in patients with symptomatic gastroesophageal reflux without esophagitis compared with those patients with grade 1 esophagitis. Moreover, abnormal GEFV function was significantly more frequent in patients with grades 2 and 3 esophagitis (Savary-Miller classification) compared with the frequency in patients with grade 1.…”
Section: Figmentioning
confidence: 99%
“…There are two relevant reports on GEFV in non-Japanese. 16,17 In one, Öberg et al, 16 stated that the length of the LES was reduced and its function became more compromised in association with changes in GEFV grade; and during 24-h pH monitoring, the holding time at pH less than 4 increased in proportion to the GEFV grade. Based on these observations, Öberg et al 16 concluded that abnormal esophageal acid exposure and esophageal mucosal injury were uncommon in patients with grade 0 gastroesophageal valves, and these findings were therefore predictive of the absence of reflux disease.…”
Section: Figmentioning
confidence: 99%